MEDIA STORAGE TECHNOLOGY USB FLASH DRIVE - Diyah Ruri Irawati (JAKSTIK Journal, 2003)
USB Flash Drive is a type of NAND-type flash memory combined with a 1.1 or USB 2.0 andused as data storage devices smaller and lighter. Because of the sophistication that has madeUSB Flash Drive becoming increasingly popular as an alternative replacement disk that hasbeen used to store data.Today USB Flash Drive measures less in length between 4-7 cm and a thickness of only 0.5 -1 cm. The user can put disaku pants or shirt. No surprise that this is now a USB Flash Driveis not only popular among the IT course, this one Device was very, very popular until theelementary school was already familiar with the USB Flash Drive as a storage medium.